Location, size and age at onset of metamorphosis in the Japanese eel Anguilla japonica. Issue 5 (14th March 2018) - Fukuda, N.; Kurogi, H.; Ambe, D.; Chow, S.; Yamamoto, T.; Yokouchi, K.; Shinoda, A.; Masuda, Y.; Sekino, M.; Saitoh, K.; Masujima, M.; Watanabe, T.; et al.
Abstract : This study clarifies the location, size and age at the onset of metamorphosis in Japanese eels Anguilla japonica through oceanic surveys, rearing experiments and analyses of the morphology and otoliths of leptocephali and glass eels. Twenty‐eight metamorphosing leptocephali were collected in the mesoscale eddy region to the east of Taiwan during research expeditions in 2004. Rearing experiments showed that the total length ( L T ) of leptocephali decreased by an average of 12·5% during metamorphosis and 13·9% during the 2–12 h after death. Thus, the mean back‐calculated L T at the onset of metamorphosis for 630 glass eels from Taiwan and Japan was estimated at 67·8 ± 2·7 mm (mean ± S.D.). The estimated mean ante‐mortem size of the fully grown pre‐metamorphic leptocephali collected in 2004 was 64·6 ± 3·4 mm, which was consistent with the L T estimate for glass eels. Otolith analysis showed that the mean age at the onset of metamorphosis was 137 ± 15 days and indicated that Japanese eels may have a recruitment route through the mesoscale eddies to the east of Taiwan in addition to the direct transfer route from the North Equatorial Current to the Kuroshio Current.